Analisis Pengaruh Shopee Video Terhadap Performa Penjualan Produk - Faisal Adi Nugroho (Asosiasi Ahli Administrasi Indonesia, 2022)
This research investigates the influence of Shopee Video on the sales performance of products among students in Bandung. Inspired by the rapidly evolving digital landscape, the study aims to explore how Shopee Video contributes to product sales performance in the student community. The research adopts a descriptive quantitative approach, employing data collection through a questionnaire. A total of 109 student respondents majoring at Bandung. Data analysis involves mean tests and regression analysis.The findings elucidate the impact of Shopee Video on product sales performance.